1982
DOI: 10.1139/f82-217
|View full text |Cite
|
Sign up to set email alerts
|

Stock Definition in Atlantic Herring (Clupea harengus harengus): Genetic Evidence for Discrete Fall and Spring Spawning Populations

Abstract: Migratory Fish Research Iflsritufe and Depcaras~serzb o j ' Z o~&~g y , U~~iversiQ of Maine ar Orcmo, Oroncr, ME 04469, USA KORNPIELD, I., B. B. SIDELL, AND P. S. GAGXON. 1982. Stock definition in Atlantic herring (Clupea haremgrxs haremgcts): genetic evidence for discrete fall and spring spawning populations. Can. J . Fish. Aquae. Sci. 39: 16310-1621.Ripe Atlantic herring (Cbupea harelagrrs harengks~s.) were sampled from seven discrete spawning grounds in the Gulf of Maine and Gulf of St. Lawrence over a peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 9 publications
1
31
0
Order By: Relevance
“…However, where Kornfield et al (1982) did not demonstrate temporal stability among annual collections from the Gulf of St. Lawrence and Gulf of Maine, King et al (1987) did demonstrate temporally stable patterns of genetic variation in North Sea herring when comparisons were based on year-classes. The contrasting results and interpretations of King et al (1987) and Kornfield et al (1982) may simply reflect the different protocols used to assess temporal variation. Although a test of hypotheses related to stability would optimally include samples from each year-class sampled across years (thus allowing a comparison among year-classes through time), the requisite material would be difficult to obtain.…”
Section: Temporal Patternmentioning
confidence: 76%
See 3 more Smart Citations
“…However, where Kornfield et al (1982) did not demonstrate temporal stability among annual collections from the Gulf of St. Lawrence and Gulf of Maine, King et al (1987) did demonstrate temporally stable patterns of genetic variation in North Sea herring when comparisons were based on year-classes. The contrasting results and interpretations of King et al (1987) and Kornfield et al (1982) may simply reflect the different protocols used to assess temporal variation. Although a test of hypotheses related to stability would optimally include samples from each year-class sampled across years (thus allowing a comparison among year-classes through time), the requisite material would be difficult to obtain.…”
Section: Temporal Patternmentioning
confidence: 76%
“…The correlation between allele frequencies of replicate samples and the genetic homogeneity among cohorts from the same location (and in most cases between collections in subsequent years) are consistent with genetic temporal stability at the scale of the spawning group. Kornfield et al (1982) concluded that it was doubtful that generational or year-class differences contributed significantly to population differentiation due to the presence of overlapping generations in the collections and the fact that Atlantic herring are iteroparous. However, where Kornfield et al (1982) did not demonstrate temporal stability among annual collections from the Gulf of St. Lawrence and Gulf of Maine, King et al (1987) did demonstrate temporally stable patterns of genetic variation in North Sea herring when comparisons were based on year-classes.…”
Section: Temporal Patternmentioning
confidence: 99%
See 2 more Smart Citations
“…This can occur even when the sampling strategy is considered optimal (e.g. spawning Atlantic herring Clupea harengus collected on the spawning grounds; Kornfield et al 1982). …”
mentioning
confidence: 99%